Dari Inovasi ke Efisiensi: Peran Inovasi Hijau dan Kesiapan Organisasi dalam Penerapan Biomassa Sekam Padi dan Dampaknya terhadap Kinerja Keberlanjutan Perusahaan - Adiluhung, Johan; Alfina Alfina; Setiawan, Wahyu Kamal (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The cement industry is an energy-intensive sector facing high energy costs, increasing pressure to reduce carbon emissions, and accelerating green transformation, making the adoption of biomass-based alternative fuels a critical strategy for improving efficiency and sustainability performance. This study aims to analyze the effects of organizational readiness and green innovation strategy on the adoption of rice husk alternative fuel and its impact on energy costs and sustainability performance at KILN2 of PT XYZ. A quantitative explanatory research design was employed, involving 55 respondents selected through total sampling. Data were collected using Likert-scale questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that organizational readiness has a positive and significant effect on alternative fuel adoption. The adoption of alternative fuel significantly reduces energy costs and enhances corporate sustainability performance. Furthermore, organizational readiness exerts a significant indirect effect on energy costs and sustainability performance through alternative fuel adoption. These findings highlight that organizational readiness is a key determinant of successful energy transition in the cement industry.